2021
DOI: 10.22541/au.162444534.46024967/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep connections: divergence histories with gene flow in mesophotic Agaricia corals

Abstract: Vastly understudied, mesophotic coral ecosystems lie below shallow reefs (> 30 m depth) and comprise ecologically distinct communities. Brooding reproductive modes appear to predominate among mesophotic-specialist species and may limit genetic connectivity among populations. Using reduced representation genomic sequencing, we assessed spatial population genetic structure (at 50 m depth) in an ecologically important mesophotic-specialist species, Agaricia grahamae among locations in the Southern Caribbean. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Hybridization and interspecific gene flow may be integral aspects of coral evolution (Hobbs et al, 2021 ; Willis et al, 2006 ). Yet, few studies have formally tested for gene flow between recent discrete taxa using demographic inference until recently (exceptions include: Cooke et al, 2020 ; Fifer et al, 2021 ; Hellberg et al, 2016 ; Ladner & Palumbi, 2012 ; Prada & Hellberg, 2020 ; Prata et al, 2022 ; Rippe et al, 2021 ). These historical analyses provide information on the speciation process and timing, including whether divergence occurred in the absence of gene flow (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization and interspecific gene flow may be integral aspects of coral evolution (Hobbs et al, 2021 ; Willis et al, 2006 ). Yet, few studies have formally tested for gene flow between recent discrete taxa using demographic inference until recently (exceptions include: Cooke et al, 2020 ; Fifer et al, 2021 ; Hellberg et al, 2016 ; Ladner & Palumbi, 2012 ; Prada & Hellberg, 2020 ; Prata et al, 2022 ; Rippe et al, 2021 ). These historical analyses provide information on the speciation process and timing, including whether divergence occurred in the absence of gene flow (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genetic studies have revealed surprising divisions and gene exchange among coral taxa, provoking re‐evaluations of both deep evolutionary relationships (Fukami et al, 2008 ; Kitahara et al, 2014 ; Ying et al, 2018 ) and relationships among closely related taxa. For example, population genomic surveys have uncovered distinct genetic clusters within Acropora (Cooke et al, 2020 ; Fifer et al, 2021 ; Rose et al, 2018 ; Underwood et al, 2020 ), Agaricia (Bongaerts et al, 2017 ; Prata et al, 2022 ), Montastraea (Rippe et al, 2021 ; Sturm et al, 2020 ), Pachyseris (Bongaerts et al, 2021 ), Pocillopora (Smith et al, 2017 ; van Oppen et al, 2018 ) and Siderastrea (Rippe et al, 2021 ), where some earlier microsatellite‐based studies had failed to detect these clusters. (For full taxonomic authorities for all species mentioned throughout this paper, see the World Register of Marine Species: www.marinespecies.org ).…”
Section: Introductionmentioning
confidence: 99%